Serum triglyceride levels are associated with recurrence in patients with acute hypertriglyceridemic pancreatitis - Guan, Langyi; Ding, Ling; Wan, Jianhua; Xia, Liang; He, Wenhua; Xiong, Huifang; Luo, Lingyu; Lu, Nonghua; Zhu, Yin (Frontiers in Medicine, 2023)
Aim To analyze the clinical profile of patients with acute hypertriglyceridemic pancreatitis (HTGP) and explore risk factors for recurrence. Methods A retrospective observational study was conducted in patients who experienced an attack of HTGP for the first time. Patients were followed until the recurrence of acute pancreatitis (AP) or 1 year. The detailed clinical profile was compared between patients with or without recurrence. Multivariate logistic regression analysis was conducted to explore independent risk factors for recurrence. Results A total of 108 HTGP patients were included in this study with 73.1% being male, and the median age being 37 (interquartile range, IQR, 30.3–44.8) years. Recurrence occurred in 70 patients (64.8%). Compared with the nonrecurrent group, serum triglyceride (TG) levels before discharge [4.1 (2.8,6.3) mmol/L vs. 2.9 (2.2,4.2) mmol/L; p = 0.002], at 1 month [3.7 (2.3,9.7) mmol/L vs. 2.0 (1.4,2.7) mmol/L; p = 0.001], at 6 months [6.1 (3.1,13.1) mmol/L vs. 2.5 (1.1,3.5) mmol/L; p = 0.003] and 12 months [9.6 (3.5,20.0) mmol/L vs. 2.7 (1.6,5.5) mmol/L; p = 0.001] after discharge were higher in the recurrent group. Poor control of TG levels (TG > 3.1 mmol/l) at the 1-month follow-up after discharge and a high Charlson’s Comorbidity Index score (≥ 2 points) increased the risk of recurrence of HTGP. Conclusion High TG levels during follow-up and Charlson’s Comorbidity Index score were independently associated with recurrence in patients with HTGP.